1967
DOI: 10.1111/j.1365-2494.1967.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

ABSORPTION OF RADIO–ACTIVE PHOSPHORUS FROM TAP–AND NODAL ROOTS OF WHITE CLOVER (TRIFOLIUM REPENS L.)

Abstract: Absorption by the tap-root and by different nodal roots of white clover SlOO and translocation of ^^P were investigated to find to what extent nodal roots can compensate for the absence of a tap-root.^P absorbed from the tap-root was distributed evenly within the whole plant. When translocation from the 2nd and 7th nodal roots was studied, similar distribution was obtained only from the nodal root closer to the centre of the plant. The backward movement of ^^P absorbed from nodal roots at the base of the plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

1982
1982
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
3
1
Order By: Relevance
“…In particular, Hoshino (1974) found that translocation of 32p absorbed by nodal roots was strongly acropetal to leaves, lateral stolon buds, and flower heads, but there was some basipetal movement to nearby lateral stolon buds. The similarity of32p distribution in this study to the results of Ueno & Williams (1967) and Hoshino (1974) strongly suggests that absorption by the stolons and subsequent translocation of phosphate has occurred.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, Hoshino (1974) found that translocation of 32p absorbed by nodal roots was strongly acropetal to leaves, lateral stolon buds, and flower heads, but there was some basipetal movement to nearby lateral stolon buds. The similarity of32p distribution in this study to the results of Ueno & Williams (1967) and Hoshino (1974) strongly suggests that absorption by the stolons and subsequent translocation of phosphate has occurred.…”
Section: Discussionsupporting
confidence: 87%
“…It has been shown that nutrients absorbed by nodal roots are translocated towards the growing point of the stolon, rather than towards the base (Stewart & Bear 1951;Nelson & Brady 1953;Ueno & Williams 1967;Hoshino 1974). In particular, Hoshino (1974) found that translocation of 32p absorbed by nodal roots was strongly acropetal to leaves, lateral stolon buds, and flower heads, but there was some basipetal movement to nearby lateral stolon buds.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation patternŝ -P distribution data show that phosphorus acquired by young and old nodal roots is actively translocated to sinks throughout clonal plants of white clover. In contrast to earlier studies (Ueno andWilliams 1967, Hoshino 1974), phosphorus distribution was not strongly dominated by acropetal movernent; rather, translocation patterns were determined largely by the modular structure of plants and by the location of source roots relative to the principal sinks within the plant. Thus, P exported from young source roots moved mainly to nearby sinks such as the stolon apex, unfolded leaves, elongating stolon tissue and young branches, while less than 20% of the P exported from old source roots moved to those sinks.…”
Section: Plant Growth Characteristicscontrasting
confidence: 90%
“…In general, previous evidence (Ueno & Williams, 1967;Hoshino, 1974;Chapman & Hay, 1993;Kemball & Marshall, 1994) indicates tbat ^^P allocation from any particular nodal root will depend in part upon its location within a plant as tbis in turn influences the relative sink strength of adjacent tissues for the transpiration stream. Tbis study bas demonstrated tbat within these constraints distribution can be modified further by tbe vascular architecture of the genotype.…”
Section: Discussionmentioning
confidence: 99%
“…As T. repens competes poorly with associated P at the organ, cell and sub-cellular levels, as yet the principles governing the distribution of recentlyassimilated P even at tbe organ level still merit attention (Chapman & Hay, 1993;Kemball & Marsball, 1994). Studies of translocation of ^^P from a single nodal root have all found movement to be predominantly acropetal when plants are making stoloniferous growth (Ueno & Williams, 1967;Hosbino, 1974;Cbapman & Hay, 1993;Kemhall & Marshall, 1994). However, the principles underlying a more detailed interpretation of the distribution of recently assimilated ^-P remain unclear, as studies report variously tbat tbe specific sites of meristematic activity and cell expansion are strong sinks (Hoshino.…”
mentioning
confidence: 99%